Evaluation of telephone first approach to demand management in English general practice: observational study. (27th September 2017) - Newbould, Jennifer; Abel, Gary; Ball, Sarah; Corbett, Jennie; Elliott, Marc; Exley, Josephine; Martin, Adam; Saunders, Catherine; Wilson, Edward; Winpenny, Eleanor; Yang, Miaoqing; Roland, Martin
Abstract : Objective  To evaluate a "telephone first" approach, in which all patients wanting to see a general practitioner (GP) are asked to speak to a GP on the phone before being given an appointment for a face to face consultation. Design  Time series and cross sectional analysis of routine healthcare data, data from national surveys, and primary survey data. Participants  147 general practices adopting the telephone first approach compared with a 10% random sample of other practices in England. Intervention  Management support for workload planning and introduction of the telephone first approach provided by two commercial companies. Main outcome measures  Number of consultations, total time consulting (59 telephone first practices, no controls). Patient experience (GP Patient Survey, telephone first practices plus controls). Use and costs of secondary care (hospital episode statistics, telephone first practices plus controls). The main analysis was intention to treat, with sensitivity analyses restricted to practices thought to be closely following the companies' protocols. Results  After the introduction of the telephone first approach, face to face consultations decreased considerably (adjusted change within practices −38%, 95% confidence interval −45% to −29%; P<0.001). An average practice experienced a 12-fold increase in telephone consultations (1204%, 633% to 2290%; P<0.001). The average duration of both telephone and face to face consultations decreased, but there was an overall increase of 8% in the mean time spent consulting by GPs, albeit with large uncertainty on this estimate (95% confidence interval −1% to 17%; P=0.088). These average workload figures mask wide variation between practices, with some practices experiencing a substantial reduction in workload and others a large increase. Compared with other English practices in the national GP Patient Survey, in practices using the telephone first approach there was a large (20.0 percentage points, 95% confidence interval 18.2 to 21.9; P<0.001) improvement in length of time to be seen. In contrast, other scores on the GP Patient Survey were slightly more negative. Introduction of the telephone first approach was followed by a small (2.0%) increase in hospital admissions (95% confidence interval 1% to 3%; P=0.006), no initial change in emergency department attendance, but a small (2% per year) decrease in the subsequent rate of rise of emergency department attendance (1% to 3%; P=0.005). There was a small net increase in secondary care costs. Conclusions  The telephone first approach shows that many problems in general practice can be dealt with over the phone. The approach does not suit all patients or practices and is not a panacea for meeting demand. There was no evidence to support claims that the approach would, on average, save costs or reduce use of secondary care.